The Struggle of Matchmaker To Find Love As Seen In Jane Austen’s Emma - Helmita Helmita; Novi Anggraini (Jurnal Ilmiah Langue and Parole, 2022)
This thesis is entitled The Struggle of Matchmaker to Find Love as Seen in Jane Austen’s Emma. The formulation of the problem in this research is how the extrinsic elements that builds the story outside the novel. How the psychology of personality of a matchmaker in finding love. The background of this research problem is in the writing of a novel created by an author, there is an author personality in creating characters in the story. Knowing the extrinsic elements that build a story will make it easier to conduct research on the psychology of the character in the story. The purposes of this research are describe the extrinsic elements that builds a novel from outside and to analyze the psychology of Emma’ personality as a matchmaker in finding love. The method used in this research is descriptive qualitative. The data are in the form of sentences and statements in the Emma and Biography of Jane Austen. The technique used in analyzing data is content analysis. The steps taken in analyzing are reading and understanding the psychology and story in the novel. This step will make it easier to research using theory extrinsic element theory of Renne Wellek and Austin Warren (1948) and personality psychology from Freud’s (1962). The results of this research there are extrinsic elements of the author which consists of literary relation with the biography, psychology, society, and idea of an author. The extrinsic elements influenced the author in creating a work on personality psychology Emma as a matchmaker in finding love consists of Id, Ego ad Superego. This research it was found that the personality of Id from Emma is more dominant and the Ego tends to follow the wishes of the Id. Superego about the principle of values and morals are also widely found. Emma really holds the values and morals of how she acts in society.